Swells over Bombay High area due to storms in the Arabian Sea - MUKHERJEE, A. K.; NARASIMHAM, A. L.; SIVARAMAKRISHNAN , T.R.; GUPTA, H. V. (MAUSAM, 1978)
An attempt is made to estimate the height and period of swells over 'Bombay High area' caused by the cyclones of the Arabian Sea. The calculated values are examined in the light of available observations and the results are discussed. Case studies of recent systems have also been made, regarding the suitability of the method used to forecast swells.